Using quality benchmarks for assessing and developing undergraduate programs - Dunn, Dana (Jossey-Bass higher and adult education series., 2011)
"Assessing student learning effectively has become a priority in higher education. Faculty and administrators must demonstrate to various constituencies and stakeholders that their programs are effective and that there is correlation between teaching and learning. This book uses selected performance criteria?benchmarks?to assist undergraduate programs to define their educational missions and goals as well as to document their effectiveness. It helps faculty and administrators use benchmarks not only to assess outcomes of student learning, but to program assessment, evaluate student learning, create meaningful faculty scholarship, ensure quality teaching, and forge connection to the community"--